Penerjemahan Seloko Adat Kota Jambi: Metode dan Kendala - Mislan Mislan; Dian Mukhlisa; Firdiansyah Firdiansyah; Rahmat Fajar; Chandri Febri Santi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Seloko is a way of life in Jambi culture. This culture is passed down from the previous generation to the next generation through speech. This culture is a long process that is obtained from the learning of the environment. Seloko is a reflection of the life of a growing community and is combined with oral art. Seloko is often conveyed in sentences using metaphorical language as well as comparative figures of speech or parables so that not everyone can fully grasp its meaning. The use of words that are difficult for ordinary people to understand is a challenge in itself to preserve this culture so that it continues to live in the latest generation, which of course has limitations in understanding the languages used and interpreting these teachings. With the existing limitations related to human resources, it is feared that this wealth will become extinct if there is no effort to archive or preserve it in other media. Efforts to disseminate information regarding the existence and wealth of this tradition should be carried out by various parties. This project is aimed at revitalizing Jambi Malay traditional seloko as an effort to internationalize oral literature. Apart from translating, this activity is focused on analyzing the methods used and the constraints they face. The theory used is the translation method theory according to Newmark (1998). Methods of data collection in the form of documentation and interviews. The results of the activity show that, in the process of translating this seloko, the difficulties faced by the writer in translating oral literature are more to the technical constraints namely: 1. Difficulty finding the right coherence of words. 2. Difficulty making appropriate rhymes.